The Malaysian image of three U.S leaders: Biden, Trump and Obama - Syed Abdullah Idid, Syed Arabi; Arandas, Mohammed Fadel; Loh, Yoke Ling (2021)
The image plays a significant role in the relationship of countries. When countries interact, citizens build images of the other country, but media events significantly prop up these images. This paper is on how Malaysians view three Presidents of the United States, namely, the present President, Joe Biden, his predecessors Donald Trump, and Barack Obama, as part of the United States' image. The relationship of the two countries, built over the years, is based on trade and education. It is Malaysia that seeks greater access to education and a better trade relationship. But a particular concern has been the Palestine issue and the global trade that Malaysia finds problematic. While the Organisation of Islamic Cooperation (OIC) champions the Palestinian case, international trade concerns Malaysia as a trading nation. Surveys raised Palestine and Global trade issues under Trump and Obama, but the public opinion on Biden added the Chinese trade issue. A study on 822 adult Malaysians nationwide in March (8 to 22 March) 2021 touched on several topics, including their opinion on the newly elected President Joe Biden. Similar surveys were done in August 2010 on Obama and in April 2017 on Trump. Biden is a stranger to the Malaysian public. When elected, Malaysians knew two characteristics of the new administration: the president as the oldest to take office and the other his deputy a woman of colour, Kamala Harris. It was a different setting from the Trump era when White supremacy was at its height. To Malaysians, the Trump administration was erratic. The practice of democracy was brought into question when Trump made severe allegations on the mismanagement of polling in the American presidential elections. We asked Malaysians what Biden could do on three issues. Was he able to solve the Palestinian issue, solve the world's economic problem and bring about trade with China? Malaysians were asked the two subjects on the two former American presidents, but the China issue was a new question this time around. A total of 27% were confident that Biden would be able to solve the Palestinian problem. On the global economy, about 35% of Malaysians were optimistic that Biden would use his good office to solve the global economy. Both Biden and Trump saw China as the main competitor on the world stage. Some 36% of Malaysians were confident Biden would be able to talk terms with China.